Draft Genome Sequences of Three Multidrug-Resistant Staphylococcus spp. Isolated from Hospital Wastewater in Malaysia - Ahmad Sabri, Nurul Syazwani (Microbiol Resour Announc, 2021)
Staphylococcus spp. are Gram-positive bacteria that reside within the normal microbiota of humans and animals but pose a health threat as reservoirs of antimicrobial resistance genes. Here, we present the draft genome sequences of three Staphylococcus sp. strains isolated from hospital wastewater in Malaysia that demonstrated resistance to multiple antibiotics.